2014
DOI: 10.1111/bjd.13058
|View full text |Cite
|
Sign up to set email alerts
|

First report of ipilimumab‐induced G rover disease

Abstract: DEAR EDITOR, Transient acantholytic dermatosis (TAD), also known as Grover disease (GD), is a papulovesicular polymorphic eruption more commonly reported in elderly white men. The main histological feature is an epidermal acantholysis associated with different degrees of dyskeratosis. The aetiology and pathogenesis remain unclear, but several local or systemic, potentially triggering conditions have been linked with this entity, including high body temperature, sweating, acute ultraviolet exposure, drug intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 10 publications
2
18
2
3
Order By: Relevance
“…We report a series of 11 patients who developed erythematous-papular eruptions during IT at our institution. 15 A particular feature seen in a subset of patients was the compromise of adnexa by the inflammatory infiltrate; this was also reported in the past in an article by Jaber et al 16 In our experience, this is an infrequent histopathological finding of cutaneous adverse events seen more often in other type of dermatoses like graft-versus-host disease. 4,9,10 This association seems to be inconsistent and variable depending on the type of agent used, even within ICI of the same family (pembrolizumab and nivolumab).…”
Section: Commentssupporting
confidence: 80%
See 1 more Smart Citation
“…We report a series of 11 patients who developed erythematous-papular eruptions during IT at our institution. 15 A particular feature seen in a subset of patients was the compromise of adnexa by the inflammatory infiltrate; this was also reported in the past in an article by Jaber et al 16 In our experience, this is an infrequent histopathological finding of cutaneous adverse events seen more often in other type of dermatoses like graft-versus-host disease. 4,9,10 This association seems to be inconsistent and variable depending on the type of agent used, even within ICI of the same family (pembrolizumab and nivolumab).…”
Section: Commentssupporting
confidence: 80%
“…To our knowledge, the latter is the second case of such nature reported in the English-language literature. 15 A particular feature seen in a subset of patients was the compromise of adnexa by the inflammatory infiltrate; this was also reported in the past in an article by Jaber et al 16 In our experience, this is an infrequent histopathological finding of cutaneous adverse events seen more often in other type of dermatoses like graft-versus-host disease.…”
Section: Commentssupporting
confidence: 80%
“…dermatitis herpetiformis), although infrequent type of dermatologic toxicity was encountered in one patient receiving ipilimumab . Lesions associated with altered keratinocytes include Grover's disease and prurigo nodularis . Lesions associated with altered melanocytes or melanoma cells include vitiligo, tumoral melanosis and regression of melanocytic nevi …”
Section: Resultsmentioning
confidence: 99%
“…A systematic review of extensive GD found recent transplant in 20% of cases, and individual reports have found cases following bone marrow, renal, liver, and heart transplants . Reports of eruptions following initiation of drugs are numerous and include, but are not limited to, sulfadoxine‐pyrimethamine, recombinant IL‐4, BRAF inhibitors, ipilimumab, and other immune checkpoint inhibitors …”
Section: Review Of Etiopathogenesis Of Grover Diseasementioning
confidence: 99%